Preparation and curing process optimization of an asymmetric impregnated vacuum bag-only prepreg - Wang, Feng; Zhang, Yi Chuan; Hu, Su; Zhang, Yang (Frontiers in Materials, 2022)
One of the most significant defects, porosity, has been proven to affect the properties of composites. It is critical to reduce the porosity of composite material and the curing cost while maintaining high laminate quality for vacuum bag-only (VBO) prepreg. In this paper, a rapidly cured epoxy resin system was developed, and an alkali-free glass fiber fabric prepreg suitable for vacuum bag molding was prepared by the asymmetric impregnation method. The optimal curing process for the prepreg was determined by resin curing kinetics, dielectric viscosity, initial curing temperature, and curing time of the prepreg on the laminate quality. The optimal curing profile of the prepreg was obtained. In addition, the effect of room temperature exposure time on the properties of the prepreg was also evaluated. These laminates produced by vacuum bag molding had outstanding internal quality and mechanical properties via the changes in the asymmetric impregnation process and the curing procedure.